1994
DOI: 10.1182/blood.v84.12.4257.bloodjournal84124257
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a specific HLA class II haplotype strongly associated with susceptibility to cyclosporine-dependent aplastic anemia

Abstract: Hematopoietic function of some aplastic anemia (AA) patients is dependent on the administration of cyclosporine (CyA). To investigate whether certain HLA class II genes are associated with susceptibility to such CyA-dependent AA, we determined the HLA class II alleles of 59 AA patients treated with CyA. Among 26 patients successfully treated with CyA, 13 required a small dose of CyA to maintain stable hematopoiesis. Of these 13 AA patients, 10 shared an HLA class II haplotype of DRB1*1501-DQA1*0102-DQB1*0602. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
51
1
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(55 citation statements)
references
References 13 publications
2
51
1
1
Order By: Relevance
“…Since the first report on HLA-DR antigens in AA by Chapuis et al (1986), who found an increased frequency of HLA-DR2 in AA patients, several studies have confirmed the association between the DR15 antigen and AA in adults (Chapuis et al, 1986;Nakao et al, 1994;Ilhan et al, 1995;Shao et al, 2000). More recently, a difference in the correlation of this allele in children and adults with AA was described by Fuhrer et al (2007).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Since the first report on HLA-DR antigens in AA by Chapuis et al (1986), who found an increased frequency of HLA-DR2 in AA patients, several studies have confirmed the association between the DR15 antigen and AA in adults (Chapuis et al, 1986;Nakao et al, 1994;Ilhan et al, 1995;Shao et al, 2000). More recently, a difference in the correlation of this allele in children and adults with AA was described by Fuhrer et al (2007).…”
Section: Discussionmentioning
confidence: 94%
“…An increased frequency of HLA-DR2, specifically DR15, has been reported in several (but not all) studies of AA, although these have been mostly studies on adult AA (Gluckman et al, 1981;D'Amaro et al, 1983;Chapuis et al, 1986;Nimer et al, 1994;Chiewsilp et al, 2000;Shao et al, 2000;Fuhrer et al, 2007). Some groups have shown that the presence of HLA-DR15 is associated with a good response to IST (Nakao et al, 1994;Ilhan et al, 1995;Ihan et al, 1997;Maciejewski et al, 2001;Oguz et al, 2002;Usman et al, 2004); however, a positive correlation between HLA-DR15 and the response to the combination of ATG and CyA, which is currently the standard for treating acquired AA, has not yet to be clearly demonstrated because the number of patients studied has been relatively small and the drugs used for IST have not been consistent (Nakao et al, 1994;Ilhan et al, 1995;Ihan et al, 1997;Shao et al, 2000;Maciejewski et al, 2001;Oguz et al, 2002;Usman et al, 2004;Fuhrer et al, 2007).…”
mentioning
confidence: 98%
“…Our data suggest that T cell-mediated autoimmunity is not HLA-restricted or genetically predisposed in MDS patients but do not exclude a role for T cell-mediated haematopoietic inhibition as suggested in several studies (Bagby, 1980;Smith & Smith, 1991;Molldrem et al, 1997b). An increased frequency of HLA DR2 (or the split DR15) has been associated with aplastic anaemia patients sensitive to cyclosporine therapy (Nakao et al, 1994). Preliminary data has suggested that a similar increase in DR15 allele frequency is also seen in MDS patients (Saunthararajah et al, 2000).…”
Section: Groupmentioning
confidence: 99%
“…Alleles of HLA-DRB1 had been determined for 20 patients whose PBMC showed high (>30%) inducibility of hsp72. Although seven of them possessed DRB1*1501, a marker for a good response to CyA (Nakao et al, 1994), 13 did not possess the marker allele (data not shown).…”
Section: High Inducibility Of Hsp72 In Pbmc Of Aa Patients and Responmentioning
confidence: 98%